2023
DOI: 10.3390/ijms241713092
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Epigenetic Changes in the Dopamine Transporter in Adult Animals Exposed to Amphetamine during Embryogenesis: Investigating Behavioral Effects

Tao Ke,
Ganesh Ambigapathy,
Thanh Ton
et al.

Abstract: The dopamine transporter (DAT) is an integral member of the dopaminergic system and is responsible for the release and reuptake of dopamine from the synaptic space into the dopaminergic neurons. DAT is also the major target of amphetamine (Amph). The effects of Amph on DAT have been intensively studied; however, the mechanisms underlying the long-term effects caused by embryonal exposure to addictive doses of Amph remain largely unexplored. As in mammals, in the nematode C. elegans Amph causes changes in locom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…However, when animals were challenged with 0.5 mM Amph for 10 min, we observed significantly increased SWIP in animals exposed to Amph during embryogenesis with respect to animals pre-exposed to control solution (Figure 2c, red and blue circles, respectively). These results confirm our previous reports [12] and resemble recent data showing that mice overexpressing TH exhibited enhanced sensitivity to Amph and elevated striatal DA levels, but no basal hyperdopaminergic behaviors [25,26]. To further investigate the Amph hypersensitivity caused by embryonal exposure to Amph, we quantified cat-2 mRNA in adult animals exposed to Amph during embryogenesis before and after the 10 min of Amph challenge.…”
Section: Exposure To Amphetamine During Embryogenesis Upregulates Pro...supporting
confidence: 89%
See 4 more Smart Citations
“…However, when animals were challenged with 0.5 mM Amph for 10 min, we observed significantly increased SWIP in animals exposed to Amph during embryogenesis with respect to animals pre-exposed to control solution (Figure 2c, red and blue circles, respectively). These results confirm our previous reports [12] and resemble recent data showing that mice overexpressing TH exhibited enhanced sensitivity to Amph and elevated striatal DA levels, but no basal hyperdopaminergic behaviors [25,26]. To further investigate the Amph hypersensitivity caused by embryonal exposure to Amph, we quantified cat-2 mRNA in adult animals exposed to Amph during embryogenesis before and after the 10 min of Amph challenge.…”
Section: Exposure To Amphetamine During Embryogenesis Upregulates Pro...supporting
confidence: 89%
“…Five H3K9-specific methyltransferases have been identified in mammals [29], and two of them, G9A and SETDB1, have C. elegans homologs, SET-25 and MET-2, respectively [28]. Recently, we showed that pharmacologic and genetic ablation of SET-25 eliminated the long-lasting behavior effects caused by embryonic exposure to Amph [12]. Here, we tested if ablation of the met-2 gene would generate similar results.…”
Section: Exposure To Amphetamine During Embryogenesis Alters Histone ...mentioning
confidence: 92%
See 3 more Smart Citations